Geochemistry of the kaolinite-rich claystone in Western Iraq - Abdulmahdi, Bashaer Hassoon; Abdulhussein, Firas Mudhafar (Iraqi Journal of Science, 2025)
It is important to spotlight the non-oil Iraqi wealth used in industry, including the kaolin clays in western Iraq, specifically in Anbar Governorate, where they are found in large quantities suitable for investment. This study focuses on the red kaolin clays found in the Hussainiyat Formation (Lower Jurassic) in the southeast of the Hussainiyat Valley. These clays are important in various industries, including ceramics, cement, and bricks. Geochemical analysis plays a an important role in determining the suitability of these clays for industrial use. Kaolinite was studied in the Northeastern Hussainiyat Area within the Hussainiyat Formation (Lower Jurassic). The presence of kaolinite and illite-smectite was noted, in addition to montmorillonite, quartz, hematite, and goethite. The concentrations of the main oxides in the study area reached Al2O3 23.35%, SiO2 51.33, Fe2O3 9.05%, MgO 1.9%, CaO 1.13%, K2O 1.34%, P2O5 0.04%, and LOI 10.2%. Aluminium in kaolin clay has a positive relationship with Cr2O3 and TiO2, a negative relationship with iron, potassium, magnesium, and sodium oxides, and a negative relationship with quartz, which increases with the decrease of these oxides. The deposits were chemically classified into shale and Fe-shale and formed in extensive weathering.